Literatura, currículo e sabores: dimensões pedagógicas no Sítio do Picapau Amarelo - Oliveira, Cintya Kelly Barroso (2018)
This research has, as object of study, the culinary culture contained in Monteiro Lobato’s works, which make up the collection Sítio do Picapau Amarelo, in particular Reinações de Narizinho (1931), Geografia de Dona Benta (1935), Memórias da Emília (1936), O Picapau Amarelo (1939) and O Minotauro (1939). The general objective is to investigate how food in the author’s work contributes for an educative discussion, specifically in relation to the cultural curriculum present in his books. It has, as specific objectives: contextualize the historical moment lived by Monteiro Lobato, verifying relations between his literature and the discussions about food present in Brazil at that time and identify how symbolic relations about food are built in that author’s work, relating them to dialogues about feeding in its pedagogical and political dimensions. This work is based on a socio-historical approach, taking as reference the basic concepts and authors guided by the following classes: collective memory Le Goff (1990); food as culture Montanari (2004), Cascudo (1983), Maciel (2004, 2005), Bezerra (2001); cultural curriculum Sacristán (2000); Hall (2003; 2000) and distinction Bourdieu (2008). The research of qualitative nature was bibliographic and analytical-descriptive; as the methodology, the Hermeneutics of Profundity was used, anchored in Thompson’s assumptions (1998), which divides the analysis in three stages: the socio-historical; the formal or discursive and the interpretation/reinterpretation. Through this study, in Monteiro Lobato’s work, an educative, forming proposal was found, and, therefore, also curricular, allying food to education, with a look upon culture. This happens because food present in the books reinforce ideological aspects which prioritize Brazilianness and the author’s ideal of a national identity and, thus, constitute an example of cultural curriculum.